Effect of surface mechanical attrition treatment on high cycle and very high cycle fatigue of a 7075-T6 aluminium alloy. (October 2020) - Gao, Tao; Sun, Zhidan; Xue, Hongqian; Retraint, Delphine
Highlights: Effects of SMAT on fatigue properties of a 7075 aluminium alloy are investigated. SMAT has beneficial effects on fatigue life in HCF but detrimental effect in VHCF. Low SMAT intensity can be optimal to protect surface from crack initiation in HCF. High SMAT intensity leads to over-peening and thus reduces fatigue life in VHCF. Abstract: Effects of surface mechanical attrition treatment (SMAT) on fatigue performance of a 7075-T6 aluminium alloy were studied in high cycle fatigue (HCF) and very high cycle fatigue (VHCF) regimes. Fatigue test results showed that SMAT can improve fatigue strength in HCF regime, but decrease it in VHCF regime. Fracture surface observations indicated that the low SMAT intensity is quite optimal, which can protect the surface from crack initiation. However, increasing SMAT intensity could lead to over-peening by inducing deep impact dimples, micro-cracks at the surface and high tensile residual stresses in the subsurface, which deteriorated fatigue performance in VHCF regime.